Molecular Epidemiology of HCV RNA Genotype-3 in Dhaka City, Bangladesh - Rahman, Md Arifur; Islam, Md Monirul; Ali, Md Eunus; Islam, Mohammad Ariful; Afroze, Farhana; Hossain, Mohammad Shamim; Rus'd, Ahmed Abu (Global Medical Genetics, 2023)
Hepatitis C virus (HCV) is a causative agent that causes chronic liver diseases worldwide. It is a little, enclosed, single-stranded ribonucleic acid (RNA) virus. The recognition of the pathogenic HCV genotype is critical for the remedy of its sufferers. The aim of this study was to identify the HCV RNA genotype to decide the correct treatment of hepatitis C positive sufferers in Bangladesh. Blood samples were collected from 390 individuals and isolated RNA (60 µg) from blood plasma. Extracted RNA was used for quantitative HCV RNA, and complementary DNA (cDNA) was prepared by polymerase chain reaction (PCR) conducted by reverse transcriptase enzyme. This cDNA amplified in multiplex by RT-PCR, which was performed with specific set of primers. The HCV RNA genotype was detected 297 of 390 patients. Of the 390 test samples, 200 (51.28%) samples were from males and 190 (48.71%) were from females, with age ranging from 5 to 78 years. In all, 166 of 200 male samples and 131/190 female samples were found positive for HCV. Of these 390 participants included in the study, 213 (54.61%) were identified as genotype 3 positive, 78 (20%) as genotype 1 positive, 6 (1.53%) as genotype 6 positive, and the remaining 93 (23.85%) samples were unclassified due to low/undetected viral load. In this study, we detected the highest percentage (30.89%) of genotype 3 HCV in patients aged 51 to 60 years. The results suggested that genotype 3 HCV is frequently present in Bangladesh and it is usually responses better to interferon therapy. However, genotype 1 and 6 HCV have also been found circulating in this country, which demands longer treatments and effective control measures.
Keywords: genotypes; cirrhosis; hepatocellular carcinoma; reverse transcription; cDNA; antiviral therapies; viral load